Effect of Soft Contact Lens Wear on Tear Film Break up Time: Doi: 10.36351/pjo.v36i2.1028 - Zaidi, Syeda Rushda; Sadiq, Mohammad Ali A; Azam, Shua; Sattar, Uzma; Iqbal, Samia; Ejaz, Huma (Pakistan Journal of Ophthalmology, 2020)
Purpose: To see the effect of soft contact lens wears on tear breakup time. Study Design: Descriptive Observational study. Place and Duration of Study: College of Ophthalmology and Allied Vision Sciences, King Edward Medical University, Mayo Hospital, Lahore. From January to March 2016. Material and Methods: Students of King Edward Medical University Lahore wearing soft contact lens for more than 3 months with no known ocular pathology were selected by non-probability convenient sampling technique. Subjects with history of using any eye drops, history of oral drugs, which could cause dry eye and individuals any ocular disease, were excluded from the study. Tear film BUT was tested by using Fluorescein sodium dye and examinig under cobalt blue filter of slit lamp.SPSS version 20 is used to analyze the data. Results: There were 30 participants with mean age of 24.5 ± 5 years. All were females. Sixty percent were wearing corrective lenses, and 40% were wearing cosmetic lenses. Out of 30 patients wearing contact lenses, only 6.67% had marginal tear film BUT and none of the patients has shown dry eyes. Individuals using contact lenses for 9 – 12 years had decreased BUT as compared to subjects using lenses for 3 – 6 months. 33.33% of extended lens wearers had reduced BUT as compared to disposable and daily wearers of contact lenses. Discomfort with contact lenses was observed in only 4 patients. Conclusion: As the duration of contact lens wear increases, the tear film break up time decreases. Individuals using extended wear contact lenses are more prone to develop decreased TFBUT.